An effect of anti-stress feed additives on broiler productivity and meat quality - E. A. Miftakhutdinova; S. L. Tikhonov; N. V. Tikhonova; R. T. Timakova (Теория и практика переработки мяса)
The paper presents the study on an impact of feed additives Peak anti-stress and SPAO (SPAO-complex) with different lithium content on meat productivity and meat quality of broiler chickens. The feed additives exert a pronounced metabolic effect, have adaptogen properties and allow forming a mechanism that facilitates compensation of the expenditure of the body, which significantly increases upon stress development. It was established that the average daily gain of the broiler chickens increased by 1.8% and 4.3% on the background of using SPAO-complex and Peak anti-stress, respectively, compared to the broiler chickens that did not receive the feed additives in the daily diet. It was shown that addition of feed additives with lithium into a diet led to an improvement of the indices of broiler meat productivity and meat quality: a level of yield of the carcasses of the 1st category increased up to 56.2–79.1%, high organoleptic indices of meat were ensured, the protein content in white and red chicken meat increased and functional-technological properties of minced meat improved. The use of feed additives ensured profitability of industrial poultry production; the highest indices of profitability were established upon introduction of the feed additive Peak anti-stress into a diet — up to 8.67 rubles per each ruble of expenses. The obtained results of the study should be taken into consideration in the technological processes when raising broiler chickens.